Eco-friendly inhibitor for corrosion of TMT rod in marine environment. (2022) - Sukumaran, Monikandon; Devarayan, Kesavan; Marimuthu, Ramar
Abstract: The present study describes application of Thespesia populnea extract for protection the TMT rod surface in marine environment. At first the inhibitor was extracted using ethanol from the leaves of the plant. Then the crude extract was coated on the TMT and subjected to corrosion in marine environment. The inhibitor exhibited a maximum of 95% of corrosion at 10 coatings of the inhibitor. The inhibition data obeyed Langmuir adsorption isotherm, which suggested that the inhibitor followed physical adsorption mechanism.